EVOLUTION OF INDIAN SOCIETY VIEWED THROUGH ADVERTISING LENS AND AIDED BY HOFSTEDE’S CULTURAL FRAMEWORK - Dr.Ghazal Masarrat , Dr. Issac K Varghese (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Indian society has had rapid changes post liberalization. Marketing post and pre-liberalization has undergone several changes. This research focuses on the pivotoal role culture has played in these changing times. The study explores effects of changing values between pre and post liberalization India and contributes to marketing literature. Study highlights culture and value systems that has influenced the way advertisement has changed over the years and the effects it has on consumer mindsets.